2022
DOI: 10.1002/joe.22157
|View full text |Cite
|
Sign up to set email alerts
|

Factors and challenges influencing work‐related outcomes of the enforced work from home during the COVID‐19 pandemic: Preliminary evidence from Indonesia

Abstract: This study investigates the socio‐demographic factors and work from home challenges associated with job satisfaction and work performance. Using a cross‐sectional survey design and convenience sampling, data from 482 Indonesian employees were gathered via a web‐based questionnaire. Bivariate analysis was used to assess job satisfaction and work performance differences across several socio‐demographic factors. Hierarchical linear regression was performed to identify the contribution of socio‐demographic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 69 publications
4
54
0
1
Order By: Relevance
“…In the present issue, Sutarto et al (2022) found that work from home challenges (e.g., lack of equipment, and information and communication technology support; ineffective communication; work-home interference), which were prominent during the COVID-19 pandemic, negatively affected job satisfaction, and in turn, work performance. To contribute potential solutions, two purposefully selected studies were included in the present issue to accompany Sutarto et al (2022). In particular, Mohammed et al (2022) emphasized the mediating role of mindfulness in enabling leadership dimensions to positively influence work outcomes, whereas Rahman et al (2022) highlighted that cyberloafing (e.g., browsing on social media and websites) has no direct effect on employee performance and that innovative work behavior could play a mediating role in enhancing the relationship between cyberloafing and employee performance.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In the present issue, Sutarto et al (2022) found that work from home challenges (e.g., lack of equipment, and information and communication technology support; ineffective communication; work-home interference), which were prominent during the COVID-19 pandemic, negatively affected job satisfaction, and in turn, work performance. To contribute potential solutions, two purposefully selected studies were included in the present issue to accompany Sutarto et al (2022). In particular, Mohammed et al (2022) emphasized the mediating role of mindfulness in enabling leadership dimensions to positively influence work outcomes, whereas Rahman et al (2022) highlighted that cyberloafing (e.g., browsing on social media and websites) has no direct effect on employee performance and that innovative work behavior could play a mediating role in enhancing the relationship between cyberloafing and employee performance.…”
Section: Introductionmentioning
confidence: 66%
“…In the present issue , Sutarto et al. (2022) found that work from home challenges (e.g., lack of equipment, and information and communication technology support; ineffective communication; work‐home interference), which were prominent during the COVID‐19 pandemic, negatively affected job satisfaction, and in turn, work performance. To contribute potential solutions, two purposefully selected studies were included in the present issue to accompany Sutarto et al.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Nonetheless, further investigation using primary data (interviews, surveys) remains necessary in order to enrich and validate the seminal insights gained through secondary evidence (news articles) in this study. The compounding effect of war (e.g., Ukraine and Russia conflict) on the effect of a global crisis (e.g., COVID‐19) on business and society worldwide (e.g., AL‐Abrrow et al., 2021; Arora & Patro, 2021; Bretas & Alon, 2020; Donthu & Gustafsson, 2020; Lim, 2021a, 2021b; Mello & Tomei, 2021; Quévat & Heinze, 2020; Sahoo et al., 2022; Sutarto et al., 2022) can also be investigated to extend the insights from this study.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) highlighted that COVID‐19 has transformed not only education, work, and social life, but also the ongoing digitization of bullying, wherein a rise in cyberbullying on social media was evidenced following the COVID‐19 pandemic. This study adds to the existing collection of COVID‐19 studies in GBOE (e.g., Al‐Abrrow et al., 2021; Bretas & Alon, 2020; Mello & Tomei, 2021; Sahoo et al., 2022; Sutarto et al., 2022), which remain free for download as part of Wiley's commitment to make COVID‐19 research freely accessible to the public.…”
Section: Hot Off the Pressmentioning
confidence: 99%